2005
DOI: 10.1542/peds.2005-0772
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Sleepiness in Adolescents and Young Adults: Causes, Consequences, and Treatment Strategies

Abstract: ABSTRACT. Adolescents and young adults are often excessively sleepy. This excessive sleepiness can have a profound negative effect on school performance, cognitive function, and mood and has been associated with other serious consequences such as increased incidence of automobile crashes. In this article we review available scientific knowledge about normal sleep changes in adolescents (13-22 years of age), the factors associated with chronic insufficient sleep, the effect of insufficient sleep on a variety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
199
0
16

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(221 citation statements)
references
References 126 publications
(116 reference statements)
6
199
0
16
Order By: Relevance
“…Sleep deprivation among college students is a known health problem that affects students' performance in and outside their academic pursuits, and thus their ability to achieve their goals [21] [26]. The National Sleep Foundation recommends that young adults (ages 18-25) sleep seven to nine hours per night [22].…”
Section: Sleep Healthmentioning
confidence: 99%
“…Sleep deprivation among college students is a known health problem that affects students' performance in and outside their academic pursuits, and thus their ability to achieve their goals [21] [26]. The National Sleep Foundation recommends that young adults (ages 18-25) sleep seven to nine hours per night [22].…”
Section: Sleep Healthmentioning
confidence: 99%
“…The morning period has also been shown in the literature to be the time that teenagers tend to be excessively sleepy because of late sleep patterns and adolescent biological considerations (see Wolfson et al, 2003 andMillman, 2005). Thus, GDL programs may consider prohibiting school driving during the entire GDL period (until 18 years of age).…”
Section: Chapter 6: Conclusionmentioning
confidence: 99%
“…Adolescent studies found poor communication, decreased concentration and cognitive performance, unintended sleeps, decreased motor performance, increased risk taking and changes in mood pattern, specifically depression (Millman 2005;Knutson et al 2007;Hagenauer et al 2009;Foster et al 2013;de Souza and Hidalgo 2014). This is hardly surprising, given that older teenagers show the largest discrepancy in sleep duration between free days and workdays of any age group, combined with a need for a longer sleep duration than adults.…”
Section: Introductionmentioning
confidence: 99%